(untitled) (Physical Education, Health and Social Sciences, 2026)
The novel is studied through a postcolonial lens. The study explores the traces of subversion of the Eurocentric images of Muslims and the Ottomon Empire in the selected novel. The novel Stone Women is a historical novel set in 19th century Ottoman rule. The focus is that how the muslims are represented in the selected novel. The research is done particularly in the backdrop of Eurocentric images of Muslims in Western literature. The study seeks to explore the stance of writer for retelling history. In the novel history is told from an objective view point where the writer has neither eulogized nor villainized the Muslims unlike the Western literature. Further the novel has tried to subvert the fixed stereotyped image of Ottoman Empire portrayed in the canonical texts. The study concludes that the writer has challenged the concepts of fixity of identities and cultural purity by projecting a culture that is a by-product of mimicry and hybridity of cultures. The writer has told a story of history that is not based on any prejudice or bias but rather as a creative outlet of a writer’s expression.